Income and Energy Consumption in Mexican Households - Rodriguez-Oreggia, Eduardo; Yepez-Garcia, Rigoberto Ariel (World Bank, Washington, DC, 2014)
The analysis of household energy consumption patterns is critical for evaluating public mechanisms, such as subsidies and social tariffs that aim to provide lower income earners with better access to energy sources. This paper focuses on Mexican households to analyze the relations between their levels of income, consumption of different forms of energy, and the role played by different household characteristics. Using microdata from the Mexican Income Expenditure Surveys, the paper first relate income and energy expenditure to determine the shape of this relation. It then applies OLS and Tobit models to determine how income levels affect energy consumption in relation to other covariates. The results show a positive relation for income deciles and energy consumption and some household characteristics -- pointing to differentiated mechanisms for improving energy use.